Application of the concept of the hospital safety index taking into account clinical risks in assessing the level of hospital safety in Ukraine - Shevchuk, Hanna; Guriev, Sergiy (ScienceRise: Medical Science, 2019)
The aim of the study. Provision the increasing hospitals safety in Ukraine by identifying and assessing the risk creating factors, organizational, structural, functional readiness of institutions ability to function effectively in providing medical assistance to victims in emergency situations (ЕS). Materials and methods of research. The research is based on the analysis of official WHO expert reports, information from special and scientific sources, namely: International Disaster Database (EM-DAT), Center for Natural Disaster Epidemiology Studies at the Catholic University of Leuven (Belgium), safety assessment reports Kiev City Clinical Hospital Emergency Medical Services (KCCHEMS) in 2012 and 2017. The research methods were: formal logic methods, bibliographic, experts review and evaluation, risk management and full-scale modelling. For the first time the adapted classification of HSI has been applied, taking into account the values of clinical risk, which is based on a methodology for identifying risks as an element of crisis management. Research results. The overall safety of KCCHEMS , assessed by the existing classification of HSI in both 2012 and 2017, is at a high level (A), meaning that further activities - work on the plan, the hospital will function during the ES. When applying our proposed clinical risk classification, we have significantly different results: in 2012, a C (critical risk) score, meaning that the hospital needs immediate action to increase its capacity to respond to emergencies, there is a high likelihood of termination functioning of the hospital under such conditions; in 2017 - at level B (significant risk): correction of the proposed measures is required, there is a likelihood of termination of hospital operation in the event of ES. Thus, the incomplete result of improving the safety of the KCCHEMS from the implementation of the recommended measures in 2012, which was established during the re-evaluation of this hospital in 2017, may be due not only to the incomplete implementation of these measures, but also to their speed of implementation and depth, which also proves the need for a correction of the 2017 Hospital Action Plan to improve hospital safety. Conclusions. Methodology of determining the Hospitality Safety Index, recommended by WHO, is appropriate to apply in Ukraine, increasing its effectiveness is possible with the application of the adapted classification the HSI levels, taking into account clinical risks